# If x = 2, y = 3 a

Putting value x = 2, y = 3, z = 6;

Simplifying 1st part

= -√6 + √12

Simplifying 2nd part

= √18-√6

Simplifying 3rd part

= -√12 + √18

Putting all values we get;

(-√6 + √12) – (√18 - √6) + (-√12 + √18)

-√6 + √12 – √18 + √6 – √12 + √18

= 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

The product of <sWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics